Hemodialisis kronik pada gagal ginjal terminal dengan diabetes mellitus di RSUP DR. SARDJITO - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRAK Beside continuous self peritoneal dialysis and renal transplant, hemodialysis is used to overcome terminal renal failure. Terminal renal failure is a irreversible chronic renal failure and the patients would be death if no replacement therapy was given. Diabetic chronic hemodialysis patients have a higher death rate than non diabetic. In Sardjito General Hospital, hemodialysis as replacement therapy has been used since 1985. Since then hemodialysis was increasingly used as replacement therapy. The aim of the study is to describe the characteristics of patients with chronic terminal renal failure who received chronic hemo dialysis from January 1, 1986 to December 31, 1988. During this period 27 cases of terminal renal failure were found among 187 chronic renal failure (14,4%) or 0,4% of the total in patient in the Department of Medicine. Age of cases between 27 to 62 years old, and consists of 20 male and 7 female. Glomerulonephritis was the most fregent cause of terminal renal failure. Five death were occured out of 7 diabetic cases (71%) and 6 deaths among non diabetic cases (46%), statistically not significant. It was suggested that survival rate among hemodialysis patients in Sardjito General Hospital were low.